Buffering Effects of Extended Family: A Moderated Mediation Analysis of Maternal Depression, Parenting Stress, and Early Childhood Development in West Java, Indonesia - Habiburrahman Said; Novalika Kurnia; Aline Hafidzah; Vania Delma; Fachrudin Sani (Scientia Psychiatrica, 2025)
Introduction: In low- and middle-income countries (LMICs), maternal mental health significantly impacts early childhood development (ECD). West Java, Indonesia, presents a unique cultural context where extended family involvement is ubiquitous. This study aims to elucidate the mechanism linking maternal depressive symptoms to early childhood developmental delays, focusing on the mediating role of parenting stress and the moderating role of social support from extended family. Methods: A cross-sectional analytical study was conducted in five regencies of West Java (N = 842 mother-child dyads). Children were aged 12–36 months. We utilized the Edinburgh Postnatal Depression Scale (EPDS) for depressive symptoms, the Parenting Stress Index-Short Form (PSI-SF) for stress, the Multidimensional Scale of Perceived Social Support (MSPSS) adapted for extended family, and the Ages and Stages Questionnaire (ASQ-3) for developmental monitoring. A moderated mediation model (Hayes Model 7) was tested using Structural Equation Modeling (SEM) with 5,000 bootstrap samples. Results: High maternal depressive symptoms were significantly associated with lower ECD scores (β = -0.42, p < 0.001). Parenting stress partially mediated this relationship (Indirect Effect = -0.18, 95% CI [-0.24, -0.13]). Crucially, extended family support moderated the path between depression and parenting stress (β = -0.15, p < 0.01). Specifically, the impact of depression on parenting stress was significantly dampened in households with high extended family engagement compared to those with low support. Conclusion: Parenting stress is a critical pathway through which maternal depression compromises child development. However, the collectivist family structure in West Java serves as a protective buffer. Interventions should target not only the mother but also mobilize the extended family network as a resource for 'kalyana mitra' (supportive friends/family).